Tunable linear magnetoresistance in MgO magnetic tunnel junction sensors using two pinned CoFeB electrodes - COEY, JOHN (My University, 2012)
MgO-barrier magnetic tunnel junction sensors with both CoFeB layers pinned by IrMn have been fabricated, which show a tunneling magnetoresistance (TMR) of up to 255% at room temperature. The perpendicular configuration for magnetic field sensing is set using a two-step field annealing process. The linear TMR field range and sensitivity are tuned by inserting an ultrathin Ru layer between the upper IrMn and the top-pinned CoFeB layer. The field sensitivity reaches 26%/mT, while the noise detectivity is about 90nT/ ffiffiffiffiffiffi Hz p at 10Hz for a 0.3nm Ru insertion layer. The bias dependence of the noise suggests that this is a useful design for sensor applications
PUBLISHED
Keywords: Magnetic tunnel junctions